Implementasi Peraturan Menteri Dalam Negeri Nomor 72 Tahun 2022 di Kabupaten Merauke - Berlianna Priscilla Fangohoy; Nur Jalal; Samel W Ririhena (Papsel Journal of Humanities and Policy, 2026)
This study provides an overview of the implementation of the Regulation of the Minister of Home Affairs Number 72 of 2022 in Merauke Regency. The purpose of this study is to analyze and comprehensively describe the implementation of the Regulation of the Minister of Home Affairs Number 72 of 2022 in Merauke Regency and to identify the factors inhibiting its implementation in the region. This study applies Edward C. III’s policy implementation theory and uses a qualitative research approach through in-depth interviews with 16 informants to explore their meanings, perceptions, and understandings. A semi-structured interview approach was employed to enable the researcher to obtain flexible yet focused data, as stated by Prof. Dr. Lexy J. Moleong (2014). The study utilized an interactive data analysis technique consisting of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of the Digital Population Identity (IKD) policy in Merauke Regency has been carried out in accordance with directives from the central government through a tiered and continuous communication mechanism. However, its implementation has not yet been optimal at the regional level. The main obstacles include limited socialization, low understanding and acceptance of the policy among implementers, the absence of specific Standard Operating Procedures (SOPs) for IKD, and the lack of motivation, commitment, and integrity of human resources, ICT infrastructure, and budgetary support. In addition, the social, economic, cultural, and geographical conditions of the community also hinder the utilization of IKD, resulting in its limited use and the continued dominance of physical population documents. The findings of this study emphasize the need to strengthen communication aspects, resources, implementers’ commitment, and policy adjustments to local conditions in order to achieve the objectives of the IKD policy effectively and equitably.